Determinantes da informalidade no sistema agroindustrial do leite na região de São Carlos / SP - Bánkuti, Ferenc Istvan (2007)
Informality in Brazilian milk market is high and involves social and economical problems. This thesis aims to identify potential determinants of informal milk and cheese trade in the region of São Carlos /SP. It presents a descriptive statistical analysis for a set of social-economical and transactional indicators comparing two groups of rural producers: one of predominantly formal producers and another with producers highly inserted in the informal market. Moreover, transaction costs between rural producers and downstream agents in the milk chain are measured and analyzed. It is also presented institutional and organizational environments characteristics that motivate rural producer participation in the informal market and/or hinder their access to formal market. As theoretical support, it has been considered the theories of New Institutional Economics (NIE) and Transaction Cost Economics (TCE), as well as theories regarding illegal markets. Also, it has been used secondary data and literature review on milk agribusiness system. Besides that, 125 rural milk producers in the region of São Carlos/SP have been interviewed and key-agents, inserted in the regional milk agribusiness system, have provided qualitative information. It has been concluded that informality in milk market in that region is mainly due to farmers strategy of achieving better prices. Such strategy is taken either when producers trade exclusively in the informal market, or when producers trade simultaneously in formal and informal markets, thus working with a price mix. Informality is also determined by elements of informal and formal institutional environments (e.g. cultural aspects and weak enforcement mechanisms of formal fiscalization system). The measurement of transaction costs between rural producers and downstream agents has shown they are low and little representative, which indicates that such costs are not determinants of milk informality in the region. Besides that, most indicators analyzed have not been considered barriers to access formal market. Finally, it has been verified that informality is not restricted to rural producers on the margins of legal system, such as those infringing sanitary laws; instead, informality is also carried out by producers inserted in the formal market too.